Does Silybum Marianum Play a Role in the Treatment of Chronic Hepatitis C? - Torres, Marina; Rodríguez-Serrano, Federico; Rosario, David J.; Rodríguez-Pérez, Federico; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2013)
Objectives. The recent boom in patient education on chronic hepatitis C has resulted in a worldwide increase in the diagnosis of this condition. Available treatment is expensive and associated with significant side effects; therefore, many patients seek for alternative medicine. Silybum marianum is a natural herb known to mankind for over 2,000 years that has been used as a liverprotecting agent due to its antioxidant properties. The objective of this study is to evaluate the safety profile and the effects of this herb, using a commercially available extract; in the liver chemistry and viral load of hepatitis C in chronically infected patients. Methods. Patients aged 21-65 years old with a diagnosis of chronic hepatitis C who were not using antiviral therapy were asked to participate. Patients were randomized to treatment with S. marianum 160 mg orally three times a week for four weeks or to no-treatment (control). Blood tests for viral load and liver enzymes (ALT and AST) were done at randomization and at the end of treatment. Paired-t test was used to measure differences between baseline and week 4 values for ALT, AST and viral load. The percent change for ALT, AST and viral load of both groups was analyzed using the Mann Whitney statistical test. Results. 34 patients were enrolled. Men and women were equally distributed. Mean age was 50 years old. Mean baseline measurements of AST, ALT and viral load in the treatment group were 85 ± 12.41 IU/ml, 120 ± 20.57 IU/ml and 8.77± 4.12 copies x 106/ml while for the no-treatment group were 71 ± 9.46 IU/ml, 97 ± 15.35 IU/ml and 1.8 ± 0.62 copies x 106 /ml respectively. For treated subjects the mean values of AST, ALT and viral load demonstrated a decrease from baseline values, but this difference was not statistically significant. For control patients the values of ALT (p= .049), AST (p = .005) and viral load (p = .005) showed a statistically significant increase at week 4. Week 4 measurement changes from baseline values were calculated for each participant. The percent change for ALT (p = .014), AST (p = .002) and viral Ioad (p = .326) were compared between the treated and control group demonstrating a statistically significance difference for ALT and AST, but not for viral load. No side effects were reported using the herb extract. Conclusion. Sylibum marianum is a well-tolerated plant extract associated with a decrease in liver chemistries but with no apparent effect on viral load when given for 4 weeks. These results suggest that S. marianum may have a protective effect in the inflammatory response to HCV, but no role as an antiviral agent. Furtherinvestigations may consider using this plant extract for a longer period of time or as adjuvant to the standard therapy of chronic hepatitis C.